Hornerin contains a Linked Series of Ribosome-Targeting Peptide Antibiotics. Issue 1 (December 2018) - Gerstel, Ulrich; Latendorf, Ties; Bartels, Joachim; Becker, Alexander; Tholey, Andreas; Schröder, Jens-Michael
Abstract Cationic intrinsically disordered antimicrobial peptides (CIDAMPs) belong to a novel class of epithelial peptide antibiotics with microbicidal activity against various pathogens, includingPseudomonas aeruginosa, Escherichia coli, Staphylococcus aureus andCandida albicans . Here we show that treatment of distinct bacteria with different hornerin (HRNR)-derived CIDAMPs cause formation of unique cytoplasmic protein aggregates, suggesting a common intracellular mode of action. We further found that, unlike most amphipathic antimicrobial peptides, HRNR traverses bacterial membranes energy-dependently and accumulates within the cytoplasm. Strikingly, certain structurally different, HRNR-based CIDAMPs were found to bind to an identical panel of distinct bacterial ribosomal proteins, thereby manifesting features of several known classes of antibiotics. This may cause the formation of aberrant proteins and toxic protein aggregates in HRNR-treated pathogens which eventually may induce its death. Our study reveals evidence that structurally distinct CIDAMPs of an abundant body surface protein simultaneously target multiple sites of the bacterial protein synthesis machinery.